2020
DOI: 10.1073/pnas.1917777117
|View full text |Cite
|
Sign up to set email alerts
|

Predictions drive neural representations of visual events ahead of incoming sensory information

Abstract: The transmission of sensory information through the visual system takes time. As a result of these delays, the visual information available to the brain always lags behind the timing of events in the present moment. Compensating for these delays is crucial for functioning within dynamic environments, since interacting with a moving object (e.g., catching a ball) requires real-time localization of the object. One way the brain might achieve this is via prediction of anticipated events. Using time-resolved decod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 32 publications
(42 reference statements)
15
76
1
Order By: Relevance
“…Previous work showed that expectations could pre-activate the stimulus template (Blom, Feuerriegel, Johnson, Bode, & Hogendoorn, 2020;Kok, Mostert, & de Lange, 2017). Our Gaze dynamics of feature-based inhibtion 18 results resonated with these findings and indicated that expectations could modulate gaze positions even before the trial started (see Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Previous work showed that expectations could pre-activate the stimulus template (Blom, Feuerriegel, Johnson, Bode, & Hogendoorn, 2020;Kok, Mostert, & de Lange, 2017). Our Gaze dynamics of feature-based inhibtion 18 results resonated with these findings and indicated that expectations could modulate gaze positions even before the trial started (see Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Other theorists have also suggested that illusory perceptual shifts in the direction of object motion are caused by an anticipatory extrapolated representation. That is, neurons corresponding to locations ahead of a moving object are activated in advance, giving rise to perception of the moving object in that location before it reaches that location (Blom et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…But this does not occur (Kerzel, 2000;Kerzel, Jordan, & Müsseler, 2001;Whitney & Cavanagh, 2002;Whitney, Murakami, & Cavanagh, 2000). To explain this, advocates of the anticipatory extrapolation theory have suggested that the abrupt disappearance and associated luminance transient results in a correction or reset of extrapolation (Blom, Feuerriegel, Johnson, Bode, & Hogendoorn, 2020;Hogendoorn, 2020;Nijhawan, 2002Nijhawan, , 2008. We will refer to this as the transient correction hypothesis.…”
Section: Introductionmentioning
confidence: 97%
“…These studies showed that the visual system requires a certain amount of time to process incoming sensory information (Blom et al, 2020;Maunsell and Gibson, 1992). When considering the perception of moving objects, this amount of time could cause potential problems for the neurocognitive system as it rapidly needs to extrapolate the object trajectory to then rapidly plan action.…”
Section: Introductionmentioning
confidence: 99%